402 - An audit of Lithium Prescribing Practices in an Old Age PsychiatryService highlighting renal impairment in this cohort. (October 2021) - Valentine, L.; Cannon, J.; Marmion, S.; Corcoran, M.; Cryan, M.; Mc Carthy, G.; Dolan, C.
Abstract: Aims: To compare Lithium prescribing practices in a Psychiatry of Old Age (POA) Service in the North-West ofIreland among adults aged 65 years and over with best practice guidelines. Methods: Review of the literature informed development of audit standards for Lithium prescribing. These included National Institute for Clinical Excellent (NICE) 2014 guidelines, The British National Formulary(2019) and Maudsley Prescribing Guidelines (2018). Data was collected retrospectively, using an audit-specific data collection tool, from clinical files of POA team caseload, aged 65 years or more and prescribed Lithium over the past year. Results: At the time of audit in February 2020, 18 patients were prescribed lithium, 67% female, average age 74.6 years. Of those prescribed Lithium; 50% (n=9) had depression, 44% (n=8) had bipolar affective disorder (BPAD) and 6% (n=1) schizoaffective disorder. 78% (n= 14) of patients met the NICE standard of 3-monthly lithium level. Lithium levels were checkedon average 4.5 times in past year, average lithium level was 0.61mmol/L across the group and 39% (n=7) had lithium level within recommended therapeutic range (0.6-0.8mmol/L). 83% of patients (n=15) met the NICE standards of 3 monthly renal tests. Taking into consideration mostrecent blood test results, 100% (n=18) had abnormal renal function. Half (n=9) were initiated on lithium by POA service and of these, 56% (n=5) had documented renal impairment prior to initiation. Of patients on long term lithium at time of referral (n=9), almost half (n=4) had a documented history of lithium toxicity. Conclusions: The results of this audit highlight room for improvement in lithium monitoring of older adults attending POA service. Furthermore, all patients prescribed lithium had impaired renal function. This is an important finding given the associations between those admitted to hospital with COVID-19 and co- morbid kidney disease and increased risk of inpatient death. Our findings highlight the need for three monthly renal function monitoring in elderly prescribed lithiumgiven the additive adverse effects of increasing age and lithium on the kidney. Close working with specialised renal services to provide timely advice on renal management for those with renal impairment prescribed lithium is important to minimise adverse patient outcomes.